Helium Reservoirs in Iron Nanoparticles on the Lunar Surface - Cymes, Brittany A.; Burgess, Katherine D.; Stroud, Rhonda M. (Communications earth & environment, 2024)
The Moon’s surface is directly exposed to the space environment and subject to alteration by space weathering. One agent of space weathering, the solar wind, enriches the lunar surface with helium. Although we understand how helium is delivered to the Moon, certain aspects of helium concentration processes on the surface remain unknown, such as why impact-generated glass aggregates contain more helium than equally sized soil grains of other types. Here we have analyzed the contents of vesicular iron nanoparticles in lunar impact glasses using aberration-corrected scanning transmission electron microscopy and electron energy loss spectroscopy and show that the nanoparticles contain high concentrations of helium (10-24 atoms/nm3). The widespread occurrence of vesicular iron nanoparticles among lunar samples suggests that they may be an important helium reservoir. These results also suggest that space weathering of iron-rich minerals plays a role in helium sequestration on the Moon and potentially on other airless bodies.